Characterizing inter-frequency bias and signal quality for GLONASS satellites with triple-frequency transmissions. Issue 7 (1st October 2019) - Pan, Lin; Zhang, Xiaohong; Guo, Fei
Abstract: The GLONASS SVNs 702K (R09), 755 (R21) and 701K (R26) satellites currently provide G1, G2 and G3 signals. The difference between satellite clocks calculated by G1/G2 and G1/G3 ionospheric-free combinations, termed inter-frequency bias (IFB), is identified. The presence of IFB limits the application of G3 signal in precise positioning. The IFB is investigated using the datasets from 70 stations with a global distribution spanning 30 consecutive days. The epoch-wise phase-specific IFB (PIFB) estimates show periodic variations with a period of eight days and an average peak-to-peak amplitude of 0.107, 0.327 and 1.663 m for the R09, R21 and R26 satellites, respectively. The daily stable code-specific IFB (CIFB) estimates also show 8-day periodic signal. The day-to-day scattering of daily stable CIFB is 0.060–0.085 m. The estimation accuracy and prediction accuracy of PIFB are 0.025 and 0.019 m, respectively, while the corresponding statistics for the daily stable CIFB are 0.452 and 0.056 m, respectively. A modified estimation approach is developed to derive the time-varying epoch-wise CIFB. The epoch-wise CIFB and PIFB shows sub-daily periodic variations with the most notable periods of 5.625 and 11.250 h, respectively. The correction rate is 32% in terms of the prediction of the time-varying part of the epoch-wise CIFB. In addition, the signal quality is assessed from such aspects as carrier-to-noise density ratio, measurement noise and multipath errors.